Prosthetic rehabilitation with removable dentures positively influences quality of life in older patients: a systematic review - Jandenilson Alves Brígido; Wellington Luiz de Oliveira da Rosa; Rafael Guerra Lund (Brazilian Society of Geriatrics and Gerontology, 2023)
Objective: This systematic review assessed the effects of prosthetic rehabilitation with removable dentures on oral health-related quality of life (OHRQoL) in older adults. Methods: A comprehensive electronic search was conducted in the PubMed/MEDLINE, Web of Science, and Cochrane databases to identify randomized clinical trials and prospective clinical studies. The included studies evaluated the effects of prosthetic rehabilitation on OHRQoL in patients whose mean age was > 60 years. The interventions included complete dentures, implant-retained overdentures, and removable partial prostheses, with a minimum follow-up period of 1 month after prosthetic rehabilitation. Patient-reported outcome measures, specifically OHRQoL, were the primary outcome. Risk of bias was assessed using the Cochrane RoB 2 tool for randomized clinical trials and the ROBINS-I tool for prospective clinical studies. Results: Eleven articles were considered eligible for the systematic review. The findings indicated that removable dentures improved various OHRQoL domains, mainly functional limitations and physical and psychological disabilities. Retention, stability, comfort, speech, and masticatory efficiency were significantly better with implant overdentures than complete dentures, leading to higher patient satisfaction and OHRQoL. Conclusions: This systematic review suggests that prosthetic rehabilitation with removable dentures has a positive influence on OHRQoL in older patients. The findings highlight the beneficial impact of implant overdentures and fixed adhesive prostheses for enhancing functional outcomes and patient satisfaction. PROSPERO Registration: CRD42020209175.